Embrio Tafsir Al-Qur’an Nusantara di Era Klasik - Hartono; Ummi Habibatul Islamiyah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2022)
The aims of this article is to uncover the facts with an in-depth analysis of the study of archipelago qur’an interpretation as an interpretation sourced from the Holy Qur'an as a way of life for its adherents. The scientific treasures in interpreting the Qur'an continues to grow along with the ability of humans to express the meaning contained in it. This article uses the literature study method with a deep analysis so that it can be used as a foothold in interpretive scientific studies. In the archipelago, the development of interpretations from the VII-XV (classical) century became the embryo of the opening horizons of thought in the period that followed in interpreting the Qur'an as a book originating from the revelation of Almighty God. The simplicity of the classical interpretation does not reduce the substance of the verses in it but more than that, the interpretation of the Qur'an in that era has become a knowledge that is able to give a scientific style in the archipelago. Therefore, this paper will thoroughly discuss the embryo of Qur’anic interpretation in the classical period as a scientific treasure and the development of interpretation in the archipelago to be used as an analytical study of the development of interpretation in the middle and contemporary periods.